O2 Reduction on Electrodes Modified with Nitrogen Doped Carbon Nanotubes Synthesized with Different Metal Catalysts - Paez-Collio, M; Paez-Collio, M; Zagal-Moya, J; Zagal-Moya, J; Gulppi-Cabra, M; Gulppi-Cabra, M; Gonzalez-Sanchez, E; Gonzalez-Sanchez, E (Elsevier Ltd, 2016)
Nitrogen doped carbon nanotubes (N-CNTs) were synthesized by the chemical vapor deposition technique (CVD) using ferrocene and iron (II) phthalocyanine as carbon precursors and ethylendiamine as the carbon and nitrogen source. Fe2O3 nanoparticles, Co nanoparticles and MoO3 were supported on a sol-gel polymer and were used as catalyst and seed growth of the N-CNTs. The influence of the metal transition used as catalyst and the amount of ethylendiamine were studied in N-CNTs for oxygen reduction reaction (ORR) in alkaline media. The morphology of the N-CNTs was studied using scanning electron microscopy (SEM) revealing that de N-CNTs were multiwalled with averages of diameters ranging between 40 and 70 nm. The presence and type of nitrogen in the graphene grid was analyzed by means of Raman spectroscopy and X-ray photoelectron spectroscopy (XPS). The obtained results indicated that N-CNTs catalyzed by MoO3 presented the highest content of pyridinic-type nitrogen (around 39%). The electrocatalytic activity of N-CNTs for the ORR was evaluated by rotating disk electrode (RDE) technique in 0.2 M NaOH. The electrochemical results showed that N-CNTs catalyzed with 0.2 wt.% MoO3 and synthesized with 19.5 wt.% of ethylendiamine exhibited higher activity for ORR than N-CNTs catalyzed with Co nanoparticles or Fe2O3 nanoparticles. © 2016 Elsevier B.V. All rights reserved.